POLITICAL MASS EVENTS AND THEIR INFLUENCE ON THE FORMATION OF LEGAL NORMS IN SOCIETY - Svystovych, Roman (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to substantiate the impact of mass political events on changes in legislation and changes in the socio-political life of individual countries, as well as Ukraine. Results: it was established that political mass events actively influence changes in legal norms in society and the formation of new ones. At the same time, individual political mass events not only influence changes in political life, but in some cases contribute to the restructuring of most legal norms. This is due to the fact that during mass events they can involve large groups of the population, which in the future no longer allow the restoration of old political norms and institutions. It is substantiated that along with changes in legal norms, changes in the system of state administration bodies, as well as in the system of local self-government bodies, occur in the vast majority. In the vast majority, political mass events entail revolutionary transformations, which in the future contribute to the formation of new political parties and public movements. It is determined that political mass events should be understood as the form of functioning of the political system of society, which characterizes its changes in space and time; sequence of political events; a set of political subjects that ensures the functioning and development of political power and legislation in the country as a whole. Discussion: quite often mass events turn into a confrontation between participants in mass events and the authorities, and such a confrontation leads to victims both among participants in mass political events and among law enforcement officers who carry out orders to stop such mass events. A vivid example in this case is the Revolution of Dignity in Ukraine. At the same time, after that, not only legal norms have radically changed in Ukraine, but also the system of power and most of the norms of legislation that regulate the activities of law enforcement agencies have changed to a certain extent.